ANALYSIS OF STUDENT LEARNING PROBLEMS IN ENTOMOLOGY LECTURES - Hartono, Adi (Universitas Negeri Medan, 2025)
The main problem in Entomology lectures is the low level of active participation among students and their difficulty in understanding the material on insect classification and morphology. This has an impact on suboptimal learning outcomes and student interest in the field of entomology. The urgency of this research lies in the importance of identifying factors that hinder the learning process as a basis for developing more effective and relevant learning strategies. The objective of this study is to analyze students' learning problems in Entomology courses based on their own perceptions. This study uses a survey method with a descriptive quantitative approach. The main instrument is a closed-ended questionnaire covering five aspects of learning problems: understanding of material, learning media, teaching methods, availability of learning resources, and learning motivation. The research subjects consisted of 93 students from the Biology Education Program at FITK UINSU in the even semester of the 2024/2025 academic year who were enrolled in Entomology courses. The analysis results showed that 68% of students experienced difficulties in understanding insect classification material, 54% stated that learning media were uninteresting, and 47% considered the teaching methods used by lecturers to be insufficiently varied. The conclusion of this study indicates that students' learning challenges in Entomology lectures remain significant and diverse, necessitating the development of interactive learning media and innovative pedagogical strategies to enhance the effectiveness of the learning process.